Galectin-1 fosters an immunosuppressive microenvironment in colorectal cancer by reprogramming CD8(+) regulatory T cells - Cagnoni, Alejandro J. (Proc Natl Acad Sci U S A, 2021)
Colorectal cancer (CRC) represents the third most common malignancy and the second leading cause of cancer-related deaths worldwide. Although immunotherapy has taken center stage in mainstream oncology, it has shown limited clinical efficacy in CRC, generating an urgent need for discovery of new biomarkers and potential therapeutic targets. Galectin-1 (Gal-1), an endogenous glycan-binding protein, induces tolerogenic programs and contributes to tumor cell evasion of immune responses. Here, we investigated the relevance of Gal-1 in CRC and explored its modulatory activity within the CD8(+) regulatory T cell (Treg) compartment. Mice lacking Gal-1 (Lgals1(−/−)) developed a lower number of tumors and showed a decreased frequency of a particular population of CD8(+)CD122(+)PD-1(+) Tregs in the azoxymethane-dextran sodium sulfate model of colitis-associated CRC. Moreover, silencing of tumor-derived Gal-1 in the syngeneic CT26 CRC model resulted in reduced number and attenuated immunosuppressive capacity of CD8(+)CD122(+)PD-1(+) Tregs, leading to slower tumor growth. Moreover, stromal Gal-1 also influenced the fitness of CD8(+) Tregs, highlighting the contribution of both tumor and stromal-derived Gal-1 to this immunoregulatory effect. Finally, bioinformatic analysis of a colorectal adenocarcinoma from The Cancer Genome Atlas dataset revealed a particular signature characterized by high CD8(+) Treg score and elevated Gal-1 expression, which delineates poor prognosis in human CRC. Our findings identify CD8(+)CD122(+)PD-1(+) Tregs as a target of the immunoregulatory activity of Gal-1, suggesting a potential immunotherapeutic strategy for the treatment of CRC.